2019
DOI: 10.3390/ijerph16162894
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Psychological and Cognitive Outcomes after Green versus Suburban Walking: A Pilot Crossover Study

Abstract: This study investigated the acute effects of repeated walking sessions within green and suburban environments on participants’ psychological (anxiety and mood) and cognitive (directed-attention) outcomes. Twenty-three middle-aged adults (19 female) participated in a non-randomized crossover study comprised of once-weekly 50-min moderate-intensity walking sessions. Participants walked for three weeks in each of two treatment conditions: green and suburban, separated by a two-week washout period. Eleven particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 52 publications
2
40
1
Order By: Relevance
“…We expand on the results of the previous study by documenting a decrease in negative affect in addition to an increase in positive affect [46]. We also expand on those findings by showing that forest walks also led to reduced state-anxiety and perceived stress, which is consistent with other studies [59,90,91].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We expand on the results of the previous study by documenting a decrease in negative affect in addition to an increase in positive affect [46]. We also expand on those findings by showing that forest walks also led to reduced state-anxiety and perceived stress, which is consistent with other studies [59,90,91].…”
Section: Discussionsupporting
confidence: 89%
“…However, our observations differ somewhat from those of Berman et al [46] in that we did not see a significant improvement in working memory capacity as a result of walking location, nor did we see an improvement in working memory following walking in either location as compared to ADL. Other studies have also failed to see improvements in working memory in response to green exercise [59,92,93,94]. Three differences in the protocols may account for this difference in results between the current study and that to Berman et al [46].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The opposite interpretation is also possible-the positive effects of exercise and/or the environment were simply far larger than any influences of social setting. Although the design of the current study does not allow for conclusions about such environmental effects, previous research has frequently reported that greenspaces promote greater psychological improvements compared to exercise in built (real or simulated) or indoor environments [1,2,[4][5][6][7][8][9][10]14,32]. If environmental settings do indeed influence psychological outcomes in this way, considering the affective improvements observed, the current findings suggest that practitioners should not fear possible lessening impacts of group settings on the cited benefits of selecting nature/greenspace environments for boosting psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2003, green exercise research has examined the influence of environmental setting on health and wellbeing-related exercise outcomes. In comparison with equivalent forms of exercise in indoor or built environments and in laboratories while viewing environmental scenes [1], exercise in greenspaces has been shown to increase levels of directed attention [2][3][4], improve mood [4][5][6], reduce levels of frustration and arousal, increase levels of meditation [7], and improve self-reported mental health across 8 weeks [8]. Positive expectancy can enhance some of these acute effects of the environment [9].…”
Section: Introductionmentioning
confidence: 99%